Development of test instruments for the metacognition ability of linear program materials - Umroh; Yuhana, Yuyu (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
Metacognition ability has a crucial role in the learning process, especially in solving complex problems, therefore it is important to develop a metacognition ability test instrument. This study aims to provide an effective instrument in measuring students' metacognition ability in linear program materials for high school students. The method used is the R&D model of the ADDIE, with the research subject being conducted at SMAN 8 Kota Serang by involving 25 students of grade XI MIPA 2 as research subjects. The research produced four instrument questions, with an average item validity score of 0.70, indicating that the test instrument is valid. The reliability of this instrument was also well-tested, achieving a score of 0.73, which demonstrates a high level of reliability. Based on the student response questionnaire, 71% indicated that the instrument is practical for implementation. Overall, the developed test instrument can be concluded as an effective tool for measuring students' metacognitive abilities in understanding linear programming material in a high school educational setting.